HAVE PUBLIC DEBT LEVELS RESTRICTED ANTI-CORONAVIRUS FISCAL RESPONSES? EVIDENCE FROM EUROPE - Kalloub, Mohammed; Musabeh, Ahmed; Alrifai, Koutibah (Journal of Public Policy and Administration, 2020)
Purpose: This study was conducted to analyze the impact of public debt stock in 12 European countries on the size of primary[1] anti-coronavirus fiscal responses, and to explore the general characteristics of these packages in sample countries. Methodology: The sample included only countries from the European Union due to homogeneity in economic standards and legal framework beside the availability of data. However, graphical representation along with regression anlaysis were performed, our key findings indicate a significant negative impact of public debt on the size of primary anti-coronavirus fiscal response and expect a second wave of government borrowing in the near term. Findings: However, this study sheded the light on public debt confirming the importance of maintaining reasonable levels, as a policy recommendation; governments in the European Union are advised to conduct more efforts to reduce public debt stocks and to adopt new effective public financial management rules to overcome the high debt dilemma, since countries with low debt stocks have initiated the largest packages among the sample. Unique contribution to theory, practice and policy: The study recommends that employing data from different geographical areas and occasions to gather more evidence on this topic. Moreover, stimulus packages may be in effect for further periods. Therefore, a series of observations might be accumulated and utilized in panel data analysis to form a cogent evidence on this topic by future research efforts. [1] Primary fiscal responses are the first fiscal packages announced between the period between March-May 2020.